Analisis keterampilan menyimak tayangan belajar di TVRI pada peserta didik kelas V sekolah dasar - Siti Nurul Faizah; Sukarno Sukarno; Muhammad Ismail Sriyanto (Didaktika Dwija Indria, 2021)
This study aims to describe the listening skills of grade V Mangkuyudan elementary school students in the 2020/2021 academic year through learning shows on TVRI. This research uses descriptive qualitative research methods with a case study approach. Primary data were obtained directly from grade V students and teachers at Mangkuyudan elementary school Surakarta, while secondary data was in the form of documents of student work, teacher notes, and official documents in writing at Mangkuyudan elementary school which had a relationship with the focus of the research problem. Sources of data in this study were students of class V which consisted of 28 students as the research sample. The data collection technique was done by using questionnaires, interviews, and study documentation. The data validity test technique used source triangulation and technique triangulation. The data analysis technique used qualitative data analysis by Miles and Huberman's model, namely interactive analysis. The results of this study indicate that the students' listening skills are good, as evidenced by the class average score that has met the minimum completeness criteria. With the details that the value on numeration, namely mathematics, is lower than the value of other subject matter. The implication of this research is to increase the creativity of teachers to determine variations in methods, strategies, and effective media in online learning during the pandemic